(untitled) (Philologia, 2021)
The article briefly presents an example of literary representations of power by means of sexual bullying. In Pamela; or, Virtue Rewarded by S. Richardson the conflict between the social classes is symbolically mirrored by way of sexual struggles between male masters and female servants. We trace here a game between the victimizer and the victim where the purpose of the frolicking scenes seems to be merely sexual predation. At a deeper level, the sexual struggle between the protagonists speaks of the more general social pillaging of the poor by the rich in the eighteenth-century England. Finally, we show the way in which the conflict gradually gives way to peaceful cohabitation under the form of an exogamous alliance.